A new species of freshwater crab of the genus Oziotelphusa Müller, 1887 (Crustacea: Decapoda: Brachyura: Gecarcinucidae) from Tamil Nadu, southern India - Raj, Smrithy; Kumar, Appukuttannair Biju; Ng, Peter K. L. (Zootaxa, 2017)
A new species of gecarcinucid freshwater crab of the genus Oziotelphusa Müller, 1887, is described from stationary or slow-flowing bodies of water in Keeriparai near Nagercoil, in the state of Tamil Nadu in southern India. Oziotelphusa ravi, new species, is distinguished from its congeners by several distinct characters: the median tooth of the posterior margin of epistome forms a distinct bilobed tip in frontal view, the male pleonal somite 6 is narrowly trapezoidal and slightly wider than long with the lateral margins concave, the terminal segment of the male first gonopod is distinctly bent laterally (along the longitudinal axis) at an angle of about 45°, and the proximal part of the outer margin of the subterminal segment of the male first gonopod has a prominent deep concavity.